Building resilient relationships with suppliers in the B2B market - Wieteska Grażyna (Management, 2016)
The growing uncertainty of business environment that negatively influences the contemporary supply chains is one of the major challenges for today’s managers. The literature recommends the development of resistant supply chains, defining them as adaptive and flexible. However, there are a few scientific publications that directly link to the area of Supplier Relationship Management in this regard. The article aims to answer the question what is the flexibility and adaptability and how to perceive these two characteristics in terms of an upstream supply chain. The observations indicate that building relationships resistant to these disruptions with suppliers includes the formulation of appropriate strategies towards both the suppliers and the purchasing process. Their choice depends on the source of uncertainty and the costs of switching the suppliers